Magnetically Active GO-Fe3O4 Nanocomposite for Enhanced Rhodamine B Removal Efficiency - Souhuat, Alexander; Aritonang, Henry Fonda; Koleangan, Harry Steven Julius (Indonesian Journal of Chemistry, 2024)
According to the World Bank study, approximately 17–20% of water contamination is attributed to the textile industry. The quantity of waste produced increases as a result of increased productivity. Textile wastewater contains dyes such as rhodamine B (RhB), which are hazardous and challenging to remove using standard methods. Adsorption utilizing nano-adsorbents has been widely researched and developed to remove dyes from the environment because of its numerous advantages. Graphene oxide-magnetite (GO-Fe3O4) has been extensively explored as an adsorbent due to its large surface area, strong bonding, and ease of separation from water. In this study, GO-Fe3O4 was synthesized by combining GO from coconut shell with Fe3O4 from iron sand as an absorbent to lower the amount of RhB. Various analytical techniques, including XRD, SEM-EDS, TEM, FTIR, and UV-vis, were employed to examine the properties of the composites. The GO-Fe3O4 exhibited a maximum adsorption capacity of 34.590 mg/g under specific conditions, i.e., 0.5 g adsorbent dosage, pH 4, and a 2 h contact time. The adsorption followed the pseudo-second-order kinetics model with 0.00016 mg/g min adsorption rate while the adsorption isotherm followed the Langmuir model where adsorbent surfaces are spread homogeneously by forming a monolayer.